Do Executives Approach Leadership Differently When They Are Involved in Collaborative Partnerships? A Perspective from International Nongovernmental Organizations (INGOs). Issue 1 (2nd January 2019) - Boyer, Eric J.; Kolpakov, Aleksey; Schmitz, Hans Peter
Abstract: Leaders of international nongovernmental organizations (INGOs) navigate daily between the internal politics of their own organization and the external environment. Frequently, these leaders have to make decisions with regard to starting or managing a partnership or collaboration. Although there is extensive literature on collaboration, rarely have the leaders' own perceptions been the focus of analysis. This article draws on transcripts from 137 in-depth, in-person interviews with senior executives of U.S.-based INGOs. The research questions are: What leadership skills and behaviors are perceived to be important among executives of INGOs? and Do leaders view these skills and behaviors differently based on whether or not they are involved in collaborative partnerships? The results show that consensus-driven and visionary leadership are dominant across all leaders, no matter their level of involvement in collaborative partnerships. However, we find differences with regard to other leadership areas. Leaders involved in partnerships are more likely to emphasize motivational leadership and relationship management. Leaders who do not work in partnerships place more emphasis on task-oriented aspects of leadership: decisiveness, cost-effectiveness, and marketing & outreach. These results provide new insights into the possible causes of differences in leadership styles and have implications for both nonprofit and public management.